Climatic, geographic and anthropogenic factors shape the structure of bat–fruit networks in the Neotropical region - Ligo, Ana Beatriz; Laurindo, Rafael de Souza; Faria, Lucas Del Bianco; Gregorin, Renato (Austral ecology, 2024)
Natural and anthropogenic environmental gradients are associated with changes in species richness, abundance and resource use. There is increasing interest in understanding how the structure of interaction networks varies along environmental gradients, but most studies have focused on bird–plant networks, while studies on mutualistic networks formed by other vertebrate groups are scarce. Here, we compiled a database of 48 bat–fruit networks distributed in the Neotropical region and evaluated the influence of annual precipitation, annual mean temperature, latitude, altitude and human impacts on nestedness, modularity, specialization, interaction diversity and species richness. Furthermore, we characterized the distribution of the roles of bat species in networks of interactions inserted in different biomes of the Neotropical region. We found that annual mean temperature increased nestedness, but decreased modularity and diversity of interactions. In addition, the diversity of interactions was greater in areas with higher annual precipitation, with less human impact and in lower latitude regions. Plant richness increased in regions with higher annual precipitation, while latitude negatively affected both plant and bat richness. Regarding the role played by bat species, we observed that most species occupy peripheral positions and only 4% of the species acted as connectors. Consistent with previous studies that evaluated other mutualistic systems, we demonstrated that the structure of bat–fruit networks is influenced by climatic, geographic and anthropogenic factors. These findings enhance our understanding of how ecological communities are structured along an environmental gradient and allow us to understand how these systems can be affected by changes in climate and land use.